Banking system in monetary policy (Texas Journal of Multidisciplinary Studies, 2022)
Central banks play a crucial role in ensuring economic and financial stability. They conduct monetary policy to achieve low and stable inflation. In the wake of the global financial crisis, central banks have expanded their toolkits to deal with risks to financial stability and to manage volatile exchange rates. In response to the COVID-19 pandemic, central banks used an array of conventional and unconventional tools to ease monetary policy, support liquidity in key financial markets and maintain the flow of credit. Central banks need clear policy frameworks to achieve their objectives. Operational processes tailored to each country’s circumstances enhance the effectiveness of the central banks’ policies. The IMF supports countries around the world by providing policy advice and technical assistance. The global financial crisis showed that countries need to contain risks to the financial system as a whole with dedicated financial policies. Many central banks that also have a mandate to promote financial stability have upgraded their financial stability functions, including by establishing macroprudential policy frameworks